Legal Protection or Perpetrators of Crimes With the Element of Self-Defense - Iman Sejati Zendrato; Yasmirah Mandasari Saragih; Fauzan Fauzan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Legal protection is an effort made by the government to protect its citizens in accordance with legal regulations that aim to realize justice, legal certainty, and benefits. The application of law is a system that aims to regulate and protect every action or behavior that occurs within the scope of society with various norms and sanctions that are binding and coercive in order to prevent problems from occurring. Every person who commits a crime will certainly be held accountable in the form of sanctions for the violations committed. In this writing process, the normative legal research method or normative juridical method is used using a statutory approach, a conceptual approach, and a comparative approach. A crime in general can also be caused by actions or deeds that are not directly carried out with an element of intent in the form of protection or self-defense. Accountability for criminal acts on the basis of self-defense in this case can be justified as long as it meets the requirements and limitations according to legal provisions. Thus, self-defense efforts in the criminal act process cannot be punished if they meet the elements of self-protection because there is no way out, meet the unlawful nature, for the benefit of oneself, others and public order issues, and do not go against the norms that live in society.